Evaluating the complementarity of communication tools for learning platforms - Carvalho, Leonardo; Bezerra, Eduardo; Guedes, Gustavo; Assis, Laura; Lima, Leonardo; Ziviani, Artur; Porto, Fabio; Barbastefano, Rafael; Ogasawara, Eduardo (PeerJ Preprints, 2017)
Due to the constant innovations in communications tools, several educational institutions are continually evaluating the adoption of new communication tools (NCT) for their adopted learning platforms (LP). Notably, many educational institutions are interested in checking if NCT is bringing benefits in their teaching and learning process. We can state an important problem that tackles this interest as for how to identify when NCT is providing a significantly different complementary communication flow concerning the current communication tools (CCT) provided at LP. This paper presents the Mixed Graph Framework (MGF) to address the problem of measuring the complementarity of an NCT in the scenario where some CCT is already established. Since we are interested in the methodological process, we evaluated MGF using synthetic data. Our experiments observed that the MGF was able to identify whether an NCT produces significant changes in the overall communications of an LP according to some centrality measures.
Keywords: Social Media; Evaluation; Educational Organization; Communication Tools